PENGARUH KUALITAS PRODUK, KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA BENGKEL LANCAR MOTOR KLABANG BONDOWOSO - Fandiyanto, Randika; Arief, Muhammad Yahya; Ghazali, As’ad Al (Relawan Jurnal Indonesia, 2022)
Marketing is the core of all business activities, it is related to the marketing function, as a liaison between companies and consumers. The influence of product quality on consumer satisfaction becomes very important when consumer satisfaction gives birth to consumer loyalty to a product that creates a communication attitude to attract new consumers. The purpose of this study was to analyze and test the effect of product quality, trust on purchasing decisions with consumer satisfaction as an intervening variable at the Klabang Bondowoso Motor Workshop. The population in this study is the consumer of Motor Workshop. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that product quality has a significant positive effect on consumer satisfaction, Trust has a significant positive effect on consumer satisfaction, product quality has a positive but not significant effect on purchasing decisions, Trust has a significant positive effect on purchasing decisions, satisfaction consumers have a significant positive effect on consumer loyalty. The results of the indirect influence hypothesis test show that product quality on purchasing decisions through consumer satisfaction has a significant positive effect, Trust on purchasing decisions through consumer satisfaction has a significant positive effect.